IMAGINÁRIOS DE INFÂNCIA: UM ESTUDO COM BASE EM PÁGINAS DE FACEBOOK DE CENTROS MUNICIPAIS DE EDUCAÇÃO INFANTIL (CMEI) DE CASCAVEL – PR - Aquino, Camila Aparecida (2019)
This research analyzes the imaginary of childhood and child in the context of a postmodern society in which communication technologies have changed everyday life in many aspects of life. The objective was to know which words and images six Child Education Centers (CMEI) published on Facebook as well as the respective comments of the internauts in an exercise of apprehending the imaginaries of childhood and child in a phenomenological perspective. We conducted this research in the comprehensive sociology of Michel Maffesoli, in the poetic reverie of Gaston Bachelard and in the composition of the ludic by Johan Huizinga. Field research was conducted over four months through a virtual ethnography based on Christine Hine, Daniel Miller and Theophilos Rifiotis in the four-month observation period with data collection from six public profiles of early childhood education institutions on the social network Facebook, the results of the research showed us words and images of children and childhood related to imaginaries that denote the coexistence of modern and postmodern values. The modern view of the child is conceived no longer as a mini-adult as the medievals considered, but as a period of human life to play, to learn in a playful way and to be protected. On the other hand, postmodern values relate to showing what is happening within educational institutions in a perspective of transparency in what is done within institutions, quite different from the discretion of modern institutions. The choices of images for publication denote an always happy child who is sometimes spectator and passive in front of the dramatizations and fantasies of the teachers, sometimes active in the activities that involve playing and the netizens opine about the activities realized as "experts" of the infantile education. In the comments of the netizens, be they teachers or not, the strong presence of the emotional dimension was seized.